Rancang Bangun Unmanned Surface Vehicle (USV) Dengan Sistem Navigasi Berbasis Kompas Dan Estimasi A-GPS - Akbar Maulana Triezani; Didit Andri Jatmiko (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2021)
Abstract - Nowadays, there is a system called the Global Navigation Satellite System (GNSS) to estimate the position of an autonomous vehicle. However, in reality, GNSS receivers often experience disturbances related to accuracy and stability of readings with the main cause of obstruction of the GNSS receiver by objects such as thick clouds, buildings, or positions in the room. In this study, the position estimation system of the vehicle will use position reading through one of the features of the GNSS, namely the Assisted Global Positioning System (A-GPS) on the smartphone. In its design, the vehicle will use a compass as a determinant of the direction of motion to reach the waypoint accurately. The purpose of this study is to design a navigation system that can make the vehicle reach a waypoint with a better level of reliability using a compass and estimation from A-GPS. The method used in this study is to test the vehicle to reach the waypoint using distance and bearing calculations between the current position of the vehicle and the destination and then compare the results of the A-GPS estimation system with the Global Positioning System (GPS). The results of this study showed that the vehicle navigation system using A-GPS was able to produce a better position estimate than GPS with an accuracy level of 1 to 3 meters for overall navigation or with an average of 1.5 meters for the waypoints reached by the vehicle when navigating. . The vehicle has also been proven to be able to adjust the direction of motion towards the waypoint using a compass sensor with the farthest deviation from the destination bearing of 3o. The concept of this research comes from the premise of the A-GPS system that has been integrated into the smartphone to get the most relevant position data without worrying if the GNSS receiver is blocked by the weather or in a position indoors. Therefore, combining the two reading systems can produce a better estimate of the position to increase the reliability of a vehicle to navigate autonomously. In addition, the impact of this research can also be applied in various systems, one of which is for autonomous vehicle navigation. Keyword : Autonomous, A-GPS, Compass, Navigation, Waypoint.